STUDY ON THE DIVISION OF NURSE WORK SHIFTS WITH THE QUALITY OF HEALTH SERVICES IN HOSPITALS USING THE LITERATURE REVIEW METHOD - Bakator Citro Utomo; Sholichudin (Journal of Hospital Management and Services, 2025)
A shift system is a work arrangement system that provides an opportunity to take advantage of all the available time to operate work. Meanwhile, the quality of health services is the degree of perfection of health services in accordance with professional standards and service standards by using the potential resources available in hospitals or health centers in a reasonable, efficient, and effective manner. With good quality of health worker services and in accordance with what is expected by health service users, it will provide a reciprocity. The purpose of this study is to determine the work shift of nurses and the quality of health services in hospitals based on literature review. This research is a descriptive analytical research based on a literature review study. The results obtained from this study are that the relationship between work shifts and the quality of health services is indirectly related. However, through the intermediary of work stress, work fatigue, work performance, patient satisfaction, and so on.